Methylene Blue Treatment of Grafts During Cold Ischemia Time Reduces the Risk of Hepatitis C Virus Transmission. (23rd June 2018) - Helfritz, Fabian A; Bojkova, Denisa; Wanders, Verena; Kuklinski, Nina; Westhaus, Sandra; von Horn, Charlotte; Rauen, Ursula; Gallinat, Anja; Baba, Hideo A; Skyschally, Andreas; Swoboda, Sandra; Kinast, Volker; et al.
Abstract : Despite organ shortage, organs from HCV RNA-positive donors are not routinely transplanted in HCV-negative individuals. Because HCV mainly infects hepatocytes, other organs are merely contaminated with HCV. Here, we established an HCV decontamination protocol for kidneys. Abstract: Background: Although organ shortage is a rising problem, organs from hepatitis C virus (HCV) ribonucleic acid (RNA)-positive donors are not routinely transplanted in HCV-negative individuals. Because HCV only infects hepatocytes, other organs such as kidneys are merely contaminated with HCV via the blood. In this study, we established a protocol to reduce HCV virions during the cold ischemic time. Methods: Standard virological assays were used to investigate the effect of antivirals, including methylene blue (MB), in different preservation solutions. Kidneys from mini pigs were contaminated with Jc1 or HCV RNA-positive human serum. Afterwards, organs were flushed with MB. Hypothermic machine perfusion was used to optimize reduction of HCV. Results: Three different antivirals were investigated for their ability to inactivate HCV in vitro. Only MB completely inactivated HCV in the presence of all perfusion solutions. Hepatitis C virus-contaminated kidneys from mini pigs were treated with MB and hypothermic machine perfusion without any negative effect on the graft. Human liver-uPA-SCID mice did not establish HCV infection after inoculation with flow through from these kidneys. Conclusions: This proof-of-concept study is a first step to reduce transmission of infectious HCV particles in the transplant setting and might serve as a model for other relevant pathogens.